STATISTICAL-EPIDEMIOLOGICAL STUDY OF NEUROLOGICAL DISEASE MORBIDITY IN CHILDREN'S HOSPITAL - D. V. Blinov; S. I. Sandukovskaya (Эпилепсия и пароксизмальные состояния, 2016)
In current specialized literature for doctors today there is a lack of data on the incidence of neurological morbuduty in a hospital environment. The attempt to fill this gap of information for assessing the incidence was conducted based on data from medical records, patients referred for assessment and treatment in a city hospital from 2000 to 2009. Identified patterns and trends can be useful for planning of utilization of health care facilities (HCF), employment of medical personnel and the procurement of medicines, as well as for scientific researches design development.